(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
The defence of common values, and of the rule of law in particular, has become an issue of major concern for EU institutions. The emergency caused by the COVID-19 pandemic brought the EU to adopt a wide-ranging package of financial aids. Within this package, the hypothesis of linking the disbursement of EU funds to the respect for the rule of law in the Member States re-emerged. Rule of law deficiencies, indeed, are believed to disrupt the very functioning of the Union’s legal order, based as it is on mutual legal interdependence and mutual trust among its Members.